Bystander Effect: Literatur Review Respon Pengamat dalam Situasi Darurat - Farah Balqis Firdaus; Mardiawan, Oki (Bandung Conference Series: Psychology Science, 2024)
Abstract. The Bystander Effect occurs when people are less likely to help in an emergency because they believe the responsibility is shared with others present (Darley & Latané, 1968). This study aims to explore the reasons why someone might react in a certain way during an emergency, whether the situation is clear or ambiguous. Using a literature review method, factors influencing the decision to help or not were identified. Reasons for helping include empathy, sympathy, self-awareness, gender roles, moral responsibility, the absence of other bystanders, and a connection with the victim. Conversely, reasons for not helping involve the risk of physical harm, fear of negative reactions, diffusion of responsibility, and the perception that the situation is not serious enough. Abstrak. Efek Bystander terjadi ketika orang cenderung tidak membantu dalam situasi darurat karena mereka menganggap tanggung jawab dibagi dengan orang lain yang hadir (Darley & Latané, 1968). Studi ini bertujuan untuk meneliti alasan-alasan mengapa seseorang mungkin bereaksi dalam situasi darurat, baik yang jelas maupun yang ambigu. Dengan metode tinjauan literatur, faktor-faktor yang mempengaruhi keputusan untuk membantu atau tidak ditemukan. Alasan untuk membantu termasuk empati, simpati, kesadaran diri, peran gender, tanggung jawab moral, ketiadaan pengamat lain, dan hubungan dengan korban. Sebaliknya, alasan untuk tidak membantu meliputi risiko ancaman fisik, ketakutan akan reaksi negatif, pembagian tanggung jawab, dan anggapan bahwa situasi tidak cukup serius.